2015
DOI: 10.1007/s12197-015-9325-7
|View full text |Cite
|
Sign up to set email alerts
|

The day-of-the-week effect is weak: Evidence from the European real estate sector

Abstract: The day-of-the-week effect for the securitized real estate indices is investigated by employing daily data at the global, European and country level for the period 1990 to 2010. We test for daily seasonality in 12 countries using both full sample and rolling-regression techniques. While the evidence for the former is in line with the literature, the results for the latter cast severe doubts concerning the existence of any persistent day-of-the-week effects. Once we allow our sample to vary over time, the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…This will lead us to the following model: 2 Abraham ve Al-Hajji who analyzed the data of the returns of Saudi Arabian stok market by GARCH method indicated that average returns are not affected in the month Ramadan but there is a significant decrease in volatility. 3 (2013), Bampinas et al (2015) are some of the studies that this method were applied to stock anomalies.…”
Section: Methodsmentioning
confidence: 99%
“…This will lead us to the following model: 2 Abraham ve Al-Hajji who analyzed the data of the returns of Saudi Arabian stok market by GARCH method indicated that average returns are not affected in the month Ramadan but there is a significant decrease in volatility. 3 (2013), Bampinas et al (2015) are some of the studies that this method were applied to stock anomalies.…”
Section: Methodsmentioning
confidence: 99%
“…Weekend effects have been identified in the foreign-exchange and money markets, as well as in stock market returns by many scholars. Based on daily data from 1990 to 2010, in the world, Europe, and other countries, Bampinas et al (2015) investigated the weekend effect of the Securitization Real Estate Index and concluded that the average return rate on Friday is significantly higher than that on other days of the week. Chan and Woo (2012) found the evidence of reverse weekend effect when Monday exhibited the highest returns for the H-shares index in Hong Kong from 3 January 2000 to 1 August 2008.…”
Section: Weekend Effect and Reverse Weekend Effectmentioning
confidence: 99%
“…Furthermore, to the best of our knowledge, there is no literature examining the determinants of the seasonality in stock returns. Previous empirical studies examining similar issues that relate to the robustness of seasonal effects in asset returns include Sullivan et al 2001, Hansen et al 2005and Bampinas et al 2016. Sullivan et al 2001 attempted to answer whether calendar anomalies are the outcome of data mining supporting that previous studies had been using the same data set to formulate and test hypotheses.…”
Section: Introductionmentioning
confidence: 96%
“…Hansen et al 2005 claim that the seasonality phenomenon has diminished in the late 1980s (with the exception of small-cap stock indices) inspected the time path of p-values that account for data-mining biases and found significant calendar effects only in specific sub-samples of DJIA returns and standardized returns during the 20th century. Bampinas et al 2016 used rolling-regression techniques and examined daily seasonality at the European real estate sector. They found absence of persistent day-ofthe-week effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation